Handbook of new religions and cultural production - Cusack, Carole M., 1962-; Norman, Alex. (Brill Handbooks on Contemporary Religion, 2012)
The cultural products of new religions and spiritualities are frequently ignored or dismissed within academia, often stemming from a hesitation to acknowledge these movements as genuine. This volume explores the impact of new religions upon cultural production, exemplifying the theological and spiritual principles of particular movements and demonstrating their substantial impact on wider society. Contributions explore the realms of music, architecture, food, art, books, films, video games, and more. This scholarship will be of interest to those who wish to explore the gamut of modern religious expression, and those who wish to broaden their knowledge of the spiritual origins of human culture.